Identification of the Effectiveness of Land Cover in Some Areas in Borisallo Village for Conservation Measures - Abduh, A. Dwie Mochammad; Fachri, Ahrani Akbar; Muharram, Nur Qalbi Saesar; Ariandi, Rahmat; Taufik , Muh.; Ribawa, Andika Darmawangsa (Forestry Department, University of Muhammadiyah Makassar, 2024)
Indonesia has excellent land potential for the development of the agricultural sector with various levels of topography that are different for each region. Every slope of the land varies, there are nutrients that are a source of food for plant growth. This research aims to determine the effectiveness of land cover in Borisallo Village, Parangloe District, Gowa Regency. This research will be carried out from October 2023 to April 2024. Analysis of the physical properties of the soil will be carried out at the Soil Physics and Conservation Laboratory, and analysis of the chemical properties of the soil will be carried out at the Soil Chemistry and Fertility Laboratory, Department of Soil Science, Faculty of Agriculture, Hasanuddin University. In the preparation stage, literature study and data collection were carried out, then primary data and secondary data were collected. After that, the data is processed into a land unit map. Then soil samples are taken according to the points determined based on the land unit map. After taking soil samples, laboratory analysis is then carried out to analyze soil permeability, organic C, bulk density and porosity. Even though there is land cover, several areas in Borisallo village still require conservation measures to prevent landslides and erosion, especially on land that has a slope. This can be seen from the permeability value which is included in the slow category.